Impact of Construction Technology on Insurance Premiums - Ibrahim, Salma Mohamed (AUC Knowledge Fountain, 2021)
The witnessed technological advancement within the construction industry affects stakeholders in connection, inclusive of the insurance industry. Construction insurance premiums resemble the quantification of risks in construction projects and signify a portion of the construction expenses in return to securing the investment in cases of claims. Accordingly, new construction technology is expected to have an impact on the insurance premiums. In other words, the insurance industry is expected to re-evaluate the insurance premiums according to the risks borne by the new construction technology utilized in construction projects and the likelihood of claims arising. Even though prior literature acknowledges the reduction in insurance premiums as a result of enhanced on-site safety measures, including construction technology, preexisting research does not quantify the relationship between construction technology and insurance premiums. Despite that insurance premiums are expected to decrease in consequence of construction technology, new kinds of risks develop with advancing the industry. The goal of this research is to quantify the impact of construction technologies – namely building information modeling (BIM), virtual reality (VR) safety training, prefabricated and modular construction, robotic fabrication, 3D printing and construction automation, and construction site internet of things (IoT) - on accident reduction and insurance premiums. The research is conducted in two main stages. The first stage is industry research, at which interviews with construction and insurance professionals are conducted to understand the risk perception and premium evaluation criteria within the industry. The second stage is quantitative analysis, where surveys are conducted to evaluate the impact of construction technology on accident reduction and insurance premiums. This research also discusses the necessary adjustments to current insurance policies for the adoption of the above-mentioned construction technologies and provides a decision-making model to support contractors in adopting any of the above-mentioned construction technologies. It is concluded that accidents and insurance premium decrease most for robotic fabrication, 3D printing and automated construction; followed by construction site IoT; then prefabricated and modular construction; afterwards VR safety training, and finally BIM. The results also indicated that there is a positive relationship between the reduction in accidents and the reduction in insurance premium; which is expected to encourage contractors to use such new technologies. Through mathematical modeling, an equation predicting the reduction in insurance premium as a result of accident reduction was derived; which is a unique outcome of this research. In addition, an empirical mathematical model was developed to aid contractors in the go/no-go decision for using construction technologies based on profit prediction. Finally, additional discussions were presented to aid contractors in understanding other considerations related to insurance. Insurance premium reduction is not the sole determining factor for adopting construction technology, other factors include: the size of the contractor, the scale and complexity of projects, contractual obligation, moral obligation, and sustainability of construction technology.